Auswirkungen eines Kurz-Triathlons auf die arterielle Laktatkonzentration und Herzfrequenz - Ledl-Kurkowski, E.; Aigne, A. (Österreichisches Journal für Sportmedizin, 2000)
Before and after each event of a triathlon race (olympic distance) in 11 competitors the arterial lactate concentration was estimated. Additionally in 3 triathletes heart rate was registered continuously during the entire race. The arterial lactate concentration increased from 2,1+/-0,3 mmol/l before the race to 7,8+/-0,8 mmol/l after swimming and decreased thereafter to 5,6+/-2,2 mmol/l during cycling and 5,1+/-1,4 mmol/l after running. Mean individual heart rate ranged from 157 to 178 bpm during swimming, 156 to 165 bpm during cycling and 156-170 during running.